Assignment #12: Uses of Secondary Sources in the Study of English Development - Mahoney, James (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This assignment asks you to write a short essay of about 800 words in length in which you critically assess the use of secondary sources in at least three of the major works on English development that are listed in the syllabus.